Public Space Development Strategy in Bone District - Herman Herman; Heri Afian; Muh Sawir; Mustigawati Mustigawati; Jumiati Jumiati (Public Resource Innovation Management and Excellence, 2024)
This study aims to answer how public spaces in Bone Regency can develop well without any destruction, this must be implemented considering several things that could happen. In the context of the Theory of Sustainable Development Administration. Airport (airport), is an airfield used for landing and taking off aircraft, boarding and disembarking passengers, and loading and unloading cargo, and is equipped with flight safety facilities. Therefore, aviation is one of the transportation that is in great demand by service users, because it has advantages compared to other means of transportation, especially in terms of time efficiency, because it can reach areas that are far away in a short time. By using aviation, it greatly supports equality, growth and stability as a driver and motivator of national development and strengthens relations between nations. The method in this study is an administrative pattern. This study uses a descriptive qualitative method, with a focus on data collection through in-depth interviews, direct observation, and document analysis. This study aims to examine the construction process of the La Patau Bone Stadium from an administrative perspective and the principles of sustainable development.